Dose-dependent thrombus resolution due to oral plasminogen activator inhibitor (PAI)-1 inhibition with tiplaxtinin in a rat stenosis model of venous thrombosis - Baxi, Sanjiv; Crandall, David L.; Meier, Thomas R.; Wrobleski, Shirley; Hawley, Angela; Farris, Diana; Elokdah, Hassan; Sigler, Robert; Schaub, Robert G.; Wakefield, Thomas; Myers, Daniel (Thrombosis and Haemostasis, 2008)
This study aimed to evaluate a small-molecule PAI-1 inhibitor (PAI-039; tiplaxtinin) in a rodent stenosis model of venous thrombosis in a two-phase experiment. Phase 1 determined the efficacy of tiplaxtinin against Lovenox (LOV), while phase 2 determined the dose-dependent efficacy. For both phases, drug treatment began 24 hours after surgically induced venous thrombosis and continued for four days. Phase 1 animals (n = 24) receiving low-dose (LD; 1 mg/kg oral gavage) PAI-1 inhibitor demonstrated a 52% decrease in thrombus weight (TW) versus controls (p < 0.05) with significant reductions in active plasma PAI-1, while the high-dose (HD; 10 mg/kg oral gavage) group demonstrated a 23% reduction in TW versus controls. Animals treated subcutaneously with LOV (3 mg/kg) showed a 39% decrease in TW versus controls (p < 0.05). Coagulation tests (aPTT and TCT) were significantly different in LOV compared to PAI-1 inhibitor groups. PAI-039 treatment was also associated with significantly increased return of inferior vena cava blood flow four days post-thrombosis versus controls (p < 0.05). In phase 2 (n = 30), TW was reduced from the 0.5 mg/kg to 5 mg/ kg experimental groups, with the 10 mg/kg group demonstrating a paradoxical increase. The 5 mg/kg group showed statistically significant decreases in TW versus controls after four treatment days (p < 0.05). This is the first study to demonstrate dose related effects of PAI-039 on increasing thrombus resolution and inferior vena cava blood flow without adverse effects on anti-coagulation in a rat stenosis model of venous thrombosis.
Keywords: Venous thrombosis; plasminogen activator inhibitors; animal models; stenosis; deep vein thrombosis